Teaching English Vocabulary Pronounciation Using Fun-Learning for Students of SD 02 Weru - Nurulsyafikah, Nurulsyafikah; Suwarni, Andi; Said, Dian Riani (Raudhah Publisher, 2025)
This study explores the effectiveness of fun-learning techniques in improving English pronunciation among young learners. The research arises from the increasing need for engaging and interactive teaching methods to address the challenges in language acquisition, especially in pronunciation. Traditional, monotonous methods often fail to engage students and lead to low retention rates. A qualitative approach, including classroom observations and interviews with teachers and students, was used to evaluate the impact of fun-learning activities. The findings show that incorporating games, role-playing, and phonetic exercises significantly enhances pronunciation accuracy, boosts confidence, and improves overall language retention. The study emphasizes the importance of continuous teacher development to successfully apply these techniques. In conclusion, fun-learning addresses the limitations of conventional teaching and offers an innovative approach to improving pronunciation. Teachers are encouraged to adopt these strategies, with support from school administrators through resources and training.